Imprint effect in PZT thin films at compositions around the morphotropic phase boundary - Araujo, E. B. [UNESP] (2016)
Piezoeresponse force microscopy (PFM) and local piezoresponse hysteresis loops were used to study the imprint effect in PbZr1-xTixO3 thin films at compositions around the morphotropic phase boundary (MPB). Schottky barriers and mechanical coupling between film-substrate were excluded as origin for the imprint in these films. Comparing the composition dependence of the effective d33 before poling with some reports in the literature, the existence of point defects such as complex vacancies (Vpb .., VO .. and Vpb ..-VO ..) and Ti3+ centers is discussed as probable origin for the imprint effect observed here.